Estruturação populacional do camarão-rosa sobreexplotado Farfantepenaeus paulensis (Pérez Farfante, 1967) no litoral sul-sudeste brasileiro e seu significado para a conservação - Preto, Artur de Lima (2009)
Farfantepenaeus paulensis, also known as pink shrimp, is a shrimp species usually found from Ilhéus (Bahia, Brazil) to Mar Del Plata (Argentina) and represents an important employment source for many Brazilian fisher s families. The study of its population structure using morphometrical parameters and microsatellites markers may provide basis for conservation programs. The purpose of this study is to analyze the population structure of pink shrimp F. paulensis at the Brazilian coast, in the south and southeast regions, using microsatellite markers and its morphometrical parameters. The shrimps were sampled in Patos Lagoon (RS), St. Antônio Lagoon (SC), Itajaí-Açu River (SC), Babitonga Bay (SC) and Cananéia City (SP). Although univariate and multivariate morphometric analyses had shown different population structure degrees between the studied places, the results of both microsatellites markers and multivariate morphometric analyses showed the possibility of the occurrence of four F. paulensis populations. The results of this study are of great value to the development of future programs for the conservation of this species, so that this resource is not depleted by over-fishing, fishing activity guaranteed to the current generation and future generations.